2001
DOI: 10.1007/s003300100851
|View full text |Cite
|
Sign up to set email alerts
|

Image quality vs radiation dose for a flat-panel amorphous silicon detector: a phantom study

Abstract: The aim of this study was to investigate the image quality for a flat-panel amorphous silicon detector at various radiation dose settings and to compare the results with storage phosphor plates and a screen-film system. A CDRAD 2.0 contrast-detail phantom was imaged with a flat-panel detector (Philips Medical Systems, Eindhoven, The Netherlands) at three different dose levels with settings for intravenous urography. The same phantom was imaged with storage phosphor plates at a simulated system speed of 200 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 14 publications
1
36
0
Order By: Relevance
“…Effective measures include optimized source-object, source-image, and object-image distances, the avoidance of magnification and oblique projections, tight collimation to the relevant anatomy, the use of pulsed fluoroscopy with decreased image frequency, and the use of low frame rates or even last-image-hold to document angiographic endpoints [9,13]. Flat panel detectors improve image quality while reducing radiation exposure, and pre-interventional optimization of the tube angle by 3D-reconstructed contrast-enhanced MR angiography helps to avoid conventional survey aortography [11,22,23]. In particular, angiography units allowing the selection of lower pulse rates during fluoroscopy contribute to a significant reduction in the overall fluoroscopy time and the radiation dose exposure of patients undergoing UFE [9,24].…”
Section: Discussionmentioning
confidence: 99%
“…Effective measures include optimized source-object, source-image, and object-image distances, the avoidance of magnification and oblique projections, tight collimation to the relevant anatomy, the use of pulsed fluoroscopy with decreased image frequency, and the use of low frame rates or even last-image-hold to document angiographic endpoints [9,13]. Flat panel detectors improve image quality while reducing radiation exposure, and pre-interventional optimization of the tube angle by 3D-reconstructed contrast-enhanced MR angiography helps to avoid conventional survey aortography [11,22,23]. In particular, angiography units allowing the selection of lower pulse rates during fluoroscopy contribute to a significant reduction in the overall fluoroscopy time and the radiation dose exposure of patients undergoing UFE [9,24].…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there are several examples where CD phantoms have been used. 5,6 The evaluation is performed by letting human observers read and evaluate images of the phantom. From these evaluations, a graphical description of image quality, a contrast-detail curve (CD curve), can be obtained and a quantified measurement of image quality, the Image Quality Figure (IQF), can be calculated.…”
Section: Y3mentioning
confidence: 99%
“…It has been observed that, with CD phantom, there can also be large variations in subjective opinion regarding image quality between different observers. 6,7 At our Radiology department, the x-ray images are totally digitized. In the quality control program and optimization processes of this department, a matter of concern has been the ability to conduct image quality evaluations that would exclude human variations in the results.…”
Section: Y3mentioning
confidence: 99%
See 1 more Smart Citation
“…Geijer, et al (2001Geijer, et al ( , 2002 and Jansson, et al (2006) Geijer (2002) also used this method to evaluate lower dose techniques for scoliosis radiography. A traditional screen-film, digital radiography, and digital fluoroscopy system were evaluated.…”
Section: The Image Quality Figure and Visual Grading Analysismentioning
confidence: 99%